A critical reading of the myths in Oliver Hermanus’s Moffie (2019) and Christiaan Olwagen’s Kanarie (2018) - Du Plessis, Rory (University of Pretoria, 2023)
Dissertation (MA (Digital Culture and Media))--University of Pretoria, 2022.